Random Nanofracture‐Enabled Physical Unclonable Function. Issue 6 (20th April 2021) - Zhang, Taiping; Shu, Zhiwen; Zhang, Lijun; Chen, Yiqin; Feng, Zhanyong; Hu, Yueqiang; Huang, Feng; Wang, Pidong; Li, Dong; Yao, Yao; Sun, Song; Duan, Huigao
Abstract: Physical unclonable function (PUF) is promising for anticounterfeiting and security applications. In this paper, a PUF concept is demonstrated based on the stochastic generation of nanodot matrix via mechanical stripping of a gold film kirigami with arrayed nanoscale split‐ring cuts. The random occurrence of nanofracture of metallic nanoconnection at split‐ring parts results in unpredictable remaining (labeled as "1") or peeling‐off (labeled as "0") of nanodots in each unit and thus generates a unclonable binary matrix. The highest randomness, i.e., 50% nanodots remaining in binary matrix, can be achieved by tuning the width of nanoconnection. Mechanical modeling reveals that the PUF can be caused by fracture‐related variations such as the effective strength of the metallic nanoconnection and nanoscale adhesion. A quick response code (QR) can be retrieved for analysis from the dark field photograph of generated nanodot matrix based on the nanofacture‐enabled PUF using in‐house developed solver, demonstrating excellent unclonability, repeatability, and uniformity. The encoding capacity of our PUFs can be conveniently scaled up or down depending on the demands of applications, which can be beneficial to advanced authentication and identification systems with high security. Abstract : A random Au nanodisk array physical unclonable function (PUF) device are fabricated through advanced "Sketch and Peel" electron‐beam lithography. The unpredictability and unclonablity are realized by the intrinsically random fluctuation on mechanical stability for each unit cell of the array. The PUF could enable robust, scalable fabrication of advanced authentication and identification systems with high security.